EKSPLORASI FENOMENA LOKAL SEBAGAI STRATEGI PENGUATAN LITERASI SAINS - Yani Novita Sari; Yolanda Rahmadani Putri; Ena Suma Indrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Scientific literacy is an essential competency that students must possess to face the challenges of the 21st century, not only as the ability to understand scientific concepts, but also as the capacity to apply scientific knowledge in real-life contexts critically, reflectively, and responsibly. Various studies have shown that the low scientific literacy of students in Indonesia is influenced by science learning that is still abstract and lacks contextualization. Exploration of local phenomena is seen as a potential pedagogical strategy to strengthen scientific literacy through meaningful and relevant learning to students' environments. This study aims to comprehensively analyze the role of local phenomenon exploration in strengthening students' scientific literacy. The study used a qualitative approach with a literature study method on various relevant primary and secondary literature sources. Data analysis was carried out using content analysis techniques combined with thematic synthesis to identify concepts, implementation strategies, and the impact of local phenomenon-based learning on scientific literacy. The results of the study indicate that local phenomenon exploration consistently has a positive impact on improving students' conceptual understanding, critical thinking skills, science process skills, and scientific attitudes. Local phenomenon-based learning has also been shown to increase learning motivation and concern for the environment and local wisdom. Exploration of local phenomena is recommended as an effective, contextual, and sustainable science learning strategy in an effort to strengthen students' scientific literacy at various levels of education.